Experimental rationale of selection of the hypoglicemic dose of ginger dry extract on normoglycemic rats - N. М. Kononenko; V. V. Chikitkina; M. V. Sorokina; M. W. Alkhalaf (The State Expert Center of the Ministry of Health of Ukraine, 2018)
Modern regimens for treatment of type 2 diabetes include various groups of oral hypoglycemic agents, most of which could cause side effects. Pharmacological activity of these medicines with long-term use is often reduced, which indicates the need to expand the range of new antidiabetic drugs. Promising antidiabetic agents are substances of plant origin that have a wide range of pharmacological effects, minimal adverse reactions and can be an effective preventive and curative adjunct to the pharmacotherapy of diabetes mellitus. Among medicinal plants with hypoglycemic action, ginger medicinal (Zingiber officinale) is promising for the development of a new antidiabetic agent. The aim of the work was a screening study of the hypoglycemic effect of the extract of ginger. The subject of the study was a dry of Ginger extract medicinal (Medagroprom, Dnipro), obtained from ginger rhizomas by extraction with 50% alcohol and spray-drying. The substance of Ginger extract is a fine-grained powder of light brown color with a peculiar scent and sharp taste, the dry residue is not less than 95%, the content of gingerols is 5%. Screening of the effective dose of Ginger extract for hypoglycemic action was performed on intact normoglycemic rats in a dose range of 10-150 mg/kg. As a reference, the compound «Arfazetin» and metformin were used. The possible hypoglycemic effect of Ginger extract was determined after its single fasting intragastric administration. The antihyperglycemic properties of Ginger extract were studied under conditions of 20-day administration with intraperitoneal and oral glucose tolerance tests on the dynamics of glycemia and areas under glycemic curves. A single introduction of Ginger extract in a dose range of 10-150 mg/kg and comparison drug «Arfazetine» did not show a hypoglycemic effect when fasting. Against the background of 20-day extract of ginger administration at intraperitoneal glucose tolerance test it was revealed that the pronounced antihyperglycemic effect of Ginger extract begins to manifest at a dose of 80 mg/kg (40%) and remains consistently the same when a high dose is administered - 150 mg/kg (41%). On the model of oral glucose tolerance test, when using extract of ginger in doses of 80 and 100 mg/kg, almost identical oppression of acute hyperglycemia was registered at 40 and 38% at the 30th minute of the test. This indicates a pronounced antihyperglycemic effect of the study agent. In terms of antihyperglycemic activity, extract of ginger at a dose of 80 mg/kg is not inferior to metformin and significantly exceeds the compoud «Arfazetin» by 1.3 times. The obtained results are the basis for in-depth study of Ginger extract at a dose of 80 mg/kg as antidiabetic agent.